2015
DOI: 10.1515/eng-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Sandy Soil Improved with Cement and Nanosilica

Abstract: Abstract:In the literature, studies show that nanosilica particles and artificial pozzolans possessing can improve structural properties of cement-based materials. This paper studies the effect of cement and nanosilica on the engineering properties (compaction, unconfined compressive strength) of sand. Three different cement ratios (5, 9, and 14% by weight of dry sand) were mixed with four different nano silica ratios (0, 5, 10, and 15% by weight of cement), and then compacted into a cylindrical specimen. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…The most popular applicable additives are bres, including polypropylene and polyethylene [1][2][3]. Other additives used are nano particles, glass, y ash, and silica fume [4][5][6][7]. In addition, using additives remarkably reduces the project cost.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular applicable additives are bres, including polypropylene and polyethylene [1][2][3]. Other additives used are nano particles, glass, y ash, and silica fume [4][5][6][7]. In addition, using additives remarkably reduces the project cost.…”
Section: Introductionmentioning
confidence: 99%
“…This due to increase hydration of cement led to increase the bonding force between grains of soil cement. These findings are also introduced by [4][5][6], and [18][19][20]. Later, Laguros J.G [21] indicated that the cohesion as well as the angle of internal friction increase when the soils are treated with cement, the increase being higher for the granular soils than for the fine grained soils.…”
Section: Second Group Resultsmentioning
confidence: 75%
“…The addition of silica fume decreases the development of cracks on the surface of compacted clay samples which reduces the width of crack by 75%. The permeability of soil is increased with increase in silica fume content [12]. Silica fume can also be used as a non-traditional stabilizer for black cotton soil which is highly expansive in nature.…”
Section: B Silica Fumementioning
confidence: 99%